Efeito de diferentes lâminas de irrigação em genótipos de cafeeiro conilon - Bonomo, Diego Zancanella (2013)
Due to the conditions of uneven distribution of rainfall in northern Espírito Santo, Brazil, cultivation of Conilon coffee (Coffeacanephora) has been done predominantly under irrigation with highly productive crops especially coffee production in Brazil. After the irrigation system implementation it is fundamental to the success of the project to implement a system of water management in irrigated crop, requiring a correct quantification of crop water consumption. The purpose of this study was to evaluate the response of different genetic materials (clones) of Conilon coffee to different irrigation. The study aimed quantification of water consumption, as well as to estimate the crop coefficient (Kc). The research was conducted in a farm called Córrego Grande in São Mateus, Espírito Santo state, Brazil in commercial cultivation of Conilon coffee in 3 x 0.8 m spacing, conventional drip irrigated, with a flow rate of 2 L h-1 and spaced 0.5 m. The experimental design was completely randomized in a subplot design, with six plots, five subplots and four replications. The plots were irrigation corresponding to 25%, 50%, 75%, 100%, 125%, 150% of evapotranspiration for a condition of drip irrigation. The subplots were Conilon called 02, 03, 18, 153 and bamburral. Each replication was consisted of 20 plants. Data were subjected to analysis of variance and the means of treatments (subplots) were compared by Tukey test at 5% probability. The averages of the treatments (plots), were subjected to polynomial regression analysis. Regarding the growth parameters the 150% evapotranspiration blade for located irrigation was superior to the other ones. As for the first crop productivity, the percentages of irrigation applied for the maximum productivity varied according to the evaluated clone from blade percentages of 94.7% (kc = 0.947) for clone 03, percentage to 123.9% of the blade EToLoc (kc = 1.239) for clone 02.